KAJIAN LINGUISTIK HISTORIS KOMPARATIF PADA POLA PERUBAHAN BUNYI - Ida Ayu Iran Adhiti (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2019)
[Title: Linguistic Study of Comparative Historis on Sound Change Patterns] The local languages in Nusa Tenggara Timur need to be observed, analysed, constructed, and conserved. Data research phenomena is done deeply approaching especially the local languages, which exist and develop in Alor Island. The observer analyses language phenomena on pattern of sound change in the languages of Kabola, Hamap, and Klon in Alor Island. The complete data of the three language are analysed by the study of comparative historic linguistic. The observation that analyses the languages in Alor Island use the synchronous approach, to know the language development in a period. The theory is used to analyse the pattern of sound change in the languages of Kabola, Hamap, and Klon in Alor Island is Blust (2013). Hock, (1988), Crowley (1987), Chomsky (1968), Dyen (1978), Schane (1973), Bynon (1979), Antila (1972), Jeffers and Lehiste (1979), and Keraf (1996). The result of observation is hoped that the young generation as local language speaker realize and understand that their languages are the same origin of languages so they are reconstructed, developed, and conserved so that they can support national language.